Ang munting prinsesa ng dagat The little princess of the sea - Andersen, Hans Christian 1805-1875; Pastor, Boots S. Agbayani (Lampara books, 2012)
"The youngest mermaid daughter of the king in a kingdom at the bottom of the sea falls in love with a mortal prince. To fulfill her dream to be with him on land, she trades her sweet singing voice for a pair of legs, despite the rigid conditions by which she has to abide, or else her sacrifices will come to nothing. Find out in this story what becomes of the little mermaid in the company of her beloved prince--and the important moral sacrifice brings."